Enhancing CAR T-cell therapies against solid tumors: Mechanisms and reversion of resistance - Qin, Yue; Xu, Guotai (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR) T-cell therapy, belonging to adoptive immune cells therapy, utilizes engineered immunoreceptors to enhance tumor-specific killing. By now new generations of CAR T-cell therapies dramatically promote the effectiveness and robustness in leukemia cases. However, only a few CAR T-cell therapies gain FDA approval till now, which are applied to hematologic cancers. Targeting solid tumors through CAR T-cell therapies still faces many problems, such as tumor heterogeneity, antigen loss, infiltration inability and immunosuppressive micro-environment. Recent advances provide new insights about the mechanisms of CAR T-cell therapy resistance and give rise to potential reversal therapies. In this review, we mainly introduce existing barriers when treating solid tumors with CAR T-cells and discuss the methods to overcome these challenges.